Multilevel model of spatially-allocated time use for takeout food ordering behaviour - a case study. (22nd June 2021) - Li, Jingyao; Zhao, Shengchuan; Zhang, Junyi
The development of food delivery services in China has affected people's space choice of dining. However, few studies explored the influence of food delivery services in both spatial and time dimensions. To explore the activity decision-making mechanism which contains spatial and time dimensions, a weekly panel data of spatially-allocated time use was collected from undergraduate students. A multilevel spatially-allocated time use model is built and based on the principle of utility maximisation. The research results prove that the spatially-allocated time use in a whole day is a comprehensive decision-making process under the constraints of cross sections of multiday survey, life circles and individual attributes. Takeout food ordering behaviour decreases travel demand for dining and other non-essential activities. It is concluded that takeout food ordering behaviour affects individual decision-making of spatially-allocated time use in the whole day for both activity content and activity space.